2018
DOI: 10.3892/ol.2018.9123
|View full text |Cite
|
Sign up to set email alerts
|

Ulinastatin protects the lungs of COPD rats through the HMGB1/TLR4 signaling pathway

Abstract: The present study aimed to investigate the protective mechanism of ulinastatin against lung injury. Rat models with chronic obstructive pulmonary disease (COPD) were used to provide guidance for the medical treatment of this disease. The rats were divided into three groups: A control group, a model group and an experimental group (each, n=10). With the exception of the control group, all of the rats were prepared as models of COPD, using the composite molding method of smoking and intratracheal instillation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Previous studies have suggested that the light chain of IAIPs could exert its anti‐inflammatory effects by attenuating the HMGB1‐derived inflammatory cascade in adult subjects exposed to a variety of different organ‐related injury models 36‐42 . Ulinastatin (urinary trypsin inhibitor or bikunin) have been shown to attenuate lung injury in adult models secondary to chronic obstructive pulmonary disease, sepsis and lipopolysaccharide (LPS) exposure, attenuate the effects of diabetic cardiomyopathy, and reduce ischemia‐related hepatic injury and ischemia‐related forebrain injury by in part downregulating levels of HMGB1 36‐39,41,42 . Prior studies have also shown that administration of lipopolysaccharide (LPS) can stimulate the release of HMGB1 from cells of the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that the light chain of IAIPs could exert its anti‐inflammatory effects by attenuating the HMGB1‐derived inflammatory cascade in adult subjects exposed to a variety of different organ‐related injury models 36‐42 . Ulinastatin (urinary trypsin inhibitor or bikunin) have been shown to attenuate lung injury in adult models secondary to chronic obstructive pulmonary disease, sepsis and lipopolysaccharide (LPS) exposure, attenuate the effects of diabetic cardiomyopathy, and reduce ischemia‐related hepatic injury and ischemia‐related forebrain injury by in part downregulating levels of HMGB1 36‐39,41,42 . Prior studies have also shown that administration of lipopolysaccharide (LPS) can stimulate the release of HMGB1 from cells of the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…COPD, a progressive inflammatory respiratory disease, is the fourth leading cause of morbidity and mortality worldwide and will rise to the third leading cause by 2030 [ 1 ]. COPD is characterized by presence of progressive and poorly reversible airflow limitation and linked to abnormal inflammatory response to harmful particles or gases in the airways and the lungs [ 2 ]. It is reported that multiple processes such as inflammation, cellular apoptosis, oxidative stress, and abnormal cellular repair are involved in the pathogenesis of COPD [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…HMGB1 expression positively correlated with NF-B protein and mRNA lung levels and the elevated levels of HMGB1 were attenuated by intraperitoneally injected of a NF-B inhibitor in these animals [89]. Similarly, the elevated levels of lung HMGB1 protein and mRNA seen in LPS-exposed rats and cigarette smoke-exposed mice was attenuated by ulinastatin (100000 UI intravenously twice daily for 7 days), although the levels were not reduced to those seen in control animals [90].…”
Section: High-mobility Group Protein B In the Pathogenesis Of Copdmentioning
confidence: 85%
“…These cells subsequently release others proinflammatory mediators such as TNF- and IL-1 that can consequently induce airways remodelling [79,[82][83]87]. In addition, data on animal models have shown that blocking of HMGB1 and of its intracellular pathways has a protective role in mouse models lungs, although further studies are necessary to clarify this mechanistic pathway [90].…”
Section: High-mobility Group Protein B In the Pathogenesis Of Copdmentioning
confidence: 99%